Semi-Refined Carrageenan Attenuates Lipopolysaccharide-Induced Reactive Oxygen Species Production in Peripheral Blood Mononuclear Cells and Cell Membrane Alterations in Leukocytes - Posokhov, Yevgen; Onishchenko, Anatolii; Chumachenko, Tetyana; Makieieva, Nataliia; Kalashnyk-Vakulenko, Yuliia; Polikarpova, Hanna; Novikova, Viktoriia; Prokopyuk, Volodymyr; Nakonechna, Oksana; Chumachenko, Dmytro; Tkachenko, Viktoriya; Meniailov, Ievgen; et al. (Journal of Pharmacy and Nutrition Sciences, 2021)
Aim: To assess the effects of semi-refined carrageenan (E407a) on lipopolysaccharide (LPS)-induced reactive oxygen species (ROS) generation in peripheral blood mononuclear cells (PBMCs) and LPS-mediated cell membrane alterations in leukocytes. Methods: Blood samples collected from 8 intact rats were incubated with E407a (10 mg/ml), E407a (50 mg/ml), LPS (1 µg/ml), E407a (10 mg/ml) + LPS (1 µg/ml), E407a (50 mg/ml) + LPS (1 µg/ml) and without those compounds (controls) for 2 h in RPMI 1640 medium enriched with 5% fetal bovine serum. ROS generation in PBMCs obtained from the incubated samples was estimated by flow cytometry using 2’,7’-dichlorodihydrofluorescein diacetate (H2DCFDA) staining. The impact of E407a, LPS and their mixture on leukocyte cell membranes was evaluated spectrofluorimetrically using the fluorescent probe 2-(2¢-hydroxy-phenyl)-5-phenyl-1,3-oxazole. Results: Expectedly, incubation with LPS induced ROS generation in PBMCs and decreased the lipid order of cell membranes in leukocytes. E407a alone was found to alter neither ROS production in PBMCs, nor membrane lipid order in leukocytes. Semi-refined carrageenan partially reduced LPS-mediated ROS overproduction in PBMCs and cell membrane alterations in leukocytes. Conclusion: E407a attenuates LPS-induced alterations of redox homeostasis in rat PBMCs and LPS-mediated modifications of cell membrane lipid order in leukocytes.